169 THE SPECTRUM, ASSESSMENT AND DIAGNOSIS OF NEUROVASCULAR OPHTHALMIC PRESENTATIONS REFERRED TO AN ACUTE MEDICAL UNIT. (25th October 2022) - Mensch, R; Dahab, T; Barry, P; Murphy, J
Abstract: Background: Ocular emergencies may require urgent intervention to prevent vision loss. Physicians must be confident in recognizing their presentations. However, literature published in this area is lacking. Methods: This study assesses the consistency of the assessment of patients with neurovascular ophthalmic conditions in the Acute Medical Unit (AMU) at an Irish tertiary healthcare centre . Conditions of interest include retinal artery and vein occlusions, ischaemic optic neuropathies, and cranial nerve palsies (III, IV, and VI). Research questions to be addressed: 1. The percentage of patients referred from Eye Casualty Services (ECS) to the AMU with neurovascular ophthalmic presentations 2. The investigations performed to diagnose neurovascular ophthalmic conditions 3. How the diagnostic approach used in the AMU compares to that recommended by the literature 4. The accuracy of ECS referral diagnoses. This is an audit of 164 patients attending the AMU during a one-year period who were diagnosed with ophthalmological conditions. Results: Of patients studied, 58 (35%) were diagnosed with conditions of interest. The most common neurovascular ophthalmic diagnosis was cranial nerve palsy (21, 36%). Among neurovascular patients, routine laboratory investigations were performed in over 90% of cases. Routine imaging was performed in over 80% of cases. Referral diagnoses from the ECS accompanied 13 (22%) of neurovascular patients, all of which were accurate. Conclusion: Neurovascular ophthalmic conditions represent a significant proportion of ECS referrals to the AMU, and most aren't diagnosed until after leaving the ECS. Laboratory and imaging investigations may be inappropriately utilized in some cases. More research is needed in this area.